Needs Analysis of a STEM-Integrated Robotics Module on Linear Motion Using a Miniature Arakan Sahur - M. Arif Rahman Hakim; Haerul Pathoni; Syamsurizal; Ilham Falani (Jurnal Pendidikan Fisika, 2026)
This study aims to analyze the obstacles faced by physics teachers in utilizing digital technology-based learning media in the implementation of the Independent Curriculum. This study employed a quantitative research method, with a descriptive type of research. The sampling technique used was convenience sampling, involving 25 high school physics teachers who were non-randomly selected from various regions based on ease of access. Data analysis was conducted using a Likert Scale. The research procedure was carried out systematically through the stages of problem collection and literature review, instrument development and validation, questionnaire distribution using Google Forms, data collection and analysis, and interpretation of the results and drawing conclusions. Based on the results of the research data analysis that has been conducted, it was found that physics teachers generally have a positive perception of the use of digital media in learning and believe that digital media can increase interactivity and help visualize physics concepts. This study shows that the implementation of digital media in physics learning is not only influenced by the technical ability to use technology, but also by the teacher's ability to integrate technology pedagogically according to the characteristics of physics learning and the demands of the Independent Curriculum.